Study of leisure time physical activity of the Lithuanian adult population - Andrijauskaitė, Danguolė; Motiejūnaitė, Kristina; Bartkevičiūtė, Roma; Barzda, Albertas; Danilienė, Vida (Slauga. Mokslas ir praktika, 2022)
The aim of the study to determine the physical activity of the Lithuanian adult population in their leisure time. The study of leisure-time physical activity of the Lithuanian adult population was the study of the actual diet, nutrition and physical activity habits of the adult and elderly Lithuanian population and the knowledge about nutrition and physical activity, which was conducted in 2019, part; The study was conducted by the Center for Health Education and Disease Prevention in conjunction with municipal public health offices. The survey was conducted at the respondent’s homes with their oral consent. The survey was anonymous, no information had to be written to identify the respondent. Research methods: a survey using the leisure physical activity part of the GPAQ (Global Physical Activity Questionnaire). Sufficiently physically active 31 percent. men and 39 percent. women. The average duration of high-intensity PA was 125 minutes per week for men and 83 minutes per week for women. The duration of moderate-intensity PA was 200 minutes per week for men and 210 minutes per week for women. The older people, the lower the duration of high-intensity PA (both men and women) and the longer the duration of moderate-intensity PA. Primary, secondary education high-intensity PA 122 minutes per week, women – 80 minutes per week.; special higher education – 117 and 77 minutes per week; higher education – 133 and 89 minutes per week. High-intensity PA activities lasted less for women (86 minutes per week in urban areas, 74 minutes per week in rural areas) (130 minutes per week in urban areas and 104 minutes per week in rural areas).
Keywords: physical activity; physical activity questionnaires; GPAQ